Bundling measures for food systems transformation: A global, multimodel assessment - Sundiang, Marina; Oliveira, Thais Diniz; Mason-D'Croz, Daniel; Gibson, Matthew; Beier, Felicitas; Benavidez, Lauren; Bodirsky, Benjamin Leon; Bos, Astrid; Chepeliev, Maksym; Chen, David Meng-Chuen; de Lange, Thijs; Doelman, Jonathan; et al. (Elsevier, 2025)
Background Current food systems leave one in ten individuals at risk of hunger while driving unsustainable environmental impacts. Inaction risks further exacerbating negative impacts on both human and planetary health. These challenges emerge from complex system interactions, requiring approaches that engage with this complexity and consider how transformation measures interact across food systems. We aimed to quantify the magnitude and uncertainty of the impacts of key food systems transformation measures both individually and in a bundle using an ensemble of global economic models.